1964
DOI: 10.1002/zaac.19643320104
|View full text |Cite
|
Sign up to set email alerts
|

Gleichgewichtsstudien an ternären Oxidsystemen des Kupfers

Abstract: In den Systemen CuMnO, CuSiO und CuTiO sind mittels der Methode des isothermen Abbaues im Bereich direkt meßbarer Sauerstoffdrucke (vorwiegend um 1000°C) mit dem nachfolgenden Ergebnis Gleichgewichtsuntersuchungen durchgeführt worden: Für das Phasendreieck CuMnO werden bei 1000°C die Phasenverhältnisse im Bereiche CuOCu2OMn2O3Mn3O4 angegeben. Es resultieren zehn Phasenfelder, in welchen neben den Randphasen CuO, Cu2O, Mn2O3 und Mn3O4 die Verbindung CuMn2O4 sowie die beiden Phasen A und B dem jeweil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Rosenberg et al [10] investigated this system between 850 and 1100 1C in air. They reported that the phases formed from various mixtures of CuO Schmall and Mu¨ller mentioned the compound Cu 1+x Mn 1ÀxÀd O 2+d (x ¼ 0:06 and d ¼ 0:048) [11]. Driessens and Rieck have extended the temperature range investigating the interaction of CuO and MnO oxides in air between 750 and 1400 1C [12].…”
Section: Introductionmentioning
confidence: 98%
“…Rosenberg et al [10] investigated this system between 850 and 1100 1C in air. They reported that the phases formed from various mixtures of CuO Schmall and Mu¨ller mentioned the compound Cu 1+x Mn 1ÀxÀd O 2+d (x ¼ 0:06 and d ¼ 0:048) [11]. Driessens and Rieck have extended the temperature range investigating the interaction of CuO and MnO oxides in air between 750 and 1400 1C [12].…”
Section: Introductionmentioning
confidence: 98%
“…(c). Thirdly, the pseudo‐binary compounds of Cu 2 TiO 3, Cu 3 TiO 4, Cu 3 TiO 5, Cu 3 Ti 3 O and Cu 2 Ti 4 O have been reported for the Cu–Ti–O system. CuO is incompatible with TiO 2 at 950°C in air as the eutectic temperature between CuO and TiO 2 was calculated to have at 919°C in pure oxygen atmosphere .…”
Section: Resultsmentioning
confidence: 93%